Functional semi-finished fish product evaluation: organoleptic and evidence in vivo - Moldagaliyeva, Dinara; Uzakov, Yasin; Sarsembayeva, Nurzhan; Ibazhanova, Assem; Jussipbekova, Balzhan; Nurakhova, Alma; Artykbayeva, Ulbobek; Baimuratova, Mairash (Frontiers in Sustainable Food Systems, 2023)
Introduction The development of functional products is a new promising trend in the modern food industry. The research aims to confirm the quality indicators, efficacy and safety for living organisms of the developed functional semi-finished fish product—raw smoked sausage. The research was aimed at studying the characteristics of the semi-finished product obtained, including its organoleptic properties. However, it was also important to test the properties of the probiotic component added to the developed product and its effects in vivo on mice to verify the efficacy and safety of the E. coli 64 G strain. Methods Organoleptic and histological assessments of the product were performed. A series of experiments were also conducted to assess the product’s safety and functional properties. For this purpose, Enteracol was fed to white outbred laboratory mice with different concentrations of the active ingredient (Escherichia coli 64G strain). Organoleptic properties of the proposed product, such as smell, consumer view, and balanced taste, demonstrated high consumer qualities of the crude smoked sausage with a probiotic component. Results The results of the controlled prospective study confirmed that the product is safe and non-toxic to living organisms: mice state alive after consuming a created meal. At the same time, assessing the product’s antagonistic activity revealed its high protective effect (85%–100% survival rate of animals in the experimental groups compared to the control with 100% mortality). Discussion The proposed product has a stimulating effect on an organism and demonstrates the antagonistic activity against pathogenic and opportunistic bacteria established in the Enterobacteriaceae family members. The next step will be a long-term study of the product’s stimulating effect to prove its positive impact on the body.